Interdependence between iron acquisition and biofilm formation in Pseudomonas aeruginosa - Kang, Donghoon; Kirienko, Natalia V. (The journal of microbiology, 2018)
Bacterial biofilms remain a persistent threat to human healthcare due to their role in the development of antimicrobial resistance. To combat multi-drug resistant pathogens, it is crucial to enhance our understanding of not only the regulation of biofilm formation, but also its contribution to bacterial virulence. Iron acquisition lies at the crux of these two subjects. In this review, we discuss the role of iron acquisition in biofilm formation and how hosts impede this mechanism to defend against pathogens. We also discuss recent findings that suggest that biofilm formation can also have the reciprocal effect, influencing siderophore production and iron sequestration.